Fault Diagnosis Method of Workbench Feed System Combined with Digital Twin and Transfer Learning - GUO Weichao; WANG Jingqi; ZHANG Songwei; HAN Xuyang; GAO Xinqin (Journal of Harbin University of Science and Technology, 2025)
A digital twin fault migration diagnosis method for table feed systems is proposed to address the problems of complex machine tool equipment structure, few fault samples and low diagnostic accuracy in real-time fault monitoring. A digital twin system for the table feed system is constructed to provide fault samples for table feed system fault diagnosis. A multi-scale parallel one-dimensional convolutional neural network migration diagnosis model is constructed to improve the accuracy of the table feed system fault diagnosis. The feasibility of the proposed method is verified and the problem of low diagnostic accuracy caused by the scarcity of fault samples in table feed system fault diagnosis is effectively solved.